High health care costs in minority groups of older US Medicare beneficiaries with epilepsy. (6th June 2019) - Pisu, Maria; Richman, Joshua; Szaflarski, Jerzy P.; Funkhouser, Ellen; Dai, Chen; Juarez, Lucia; Faught, Edward; Martin, Roy C.
Abstract: Objective: To examine health care costs in diverse older Medicare beneficiaries with epilepsy. Methods: Using 2008‐2010 claims data, we conducted a longitudinal cohort study of a random sample of Medicare beneficiaries augmented for minority representation. Epilepsy cases (n = 36 912) had ≥1 International Classification of Diseases, Ninth Edition (ICD‐9) 345.x or ≥2 ICD‐9 780.3x claims, and ≥1 antiepileptic drug (AED) in 2009; new cases (n = 3706) had no seizure/epilepsy claims nor AEDs in the previous 365 days. Costs were measured by reimbursements for all care received. High cost was defined as follow‐up 1‐year cost ≥ 75th percentile. Logistic regressions examined association of high cost with race/ethnicity, adjusting for demographic, clinical, economic, and treatment quality factors. In cases with continuous 2‐year data, we obtained costs in two 6‐month periods before and two after the index event. Results: Cohort was ~62% African Americans (AAs), 11% Hispanics, 5% Asians, and 2% American Indian/Alaska Natives. Mean costs in the follow‐up were ~$30 000 (median = $11 547; new cases, mean = $44 642; median = $25 008). About 19% white compared to 27% AA cases had high cost. AA had higher odds of high cost in adjusted analyses (odds ratio [OR] = 1.20, 95% confidence interval [CI] = 1.11‐1.29), although this was only marginally significant when adjusting for AED adherence (OR = 1.09, 95% CI = 1.01‐1.18, P  =   0.03). Factors associated with high cost included ≥1 comorbidity, neurological care, and low AED adherence. Costs were highest at ~$17 000 in the 6 months immediately before and after the index event (>$29 000 for new cases). Significance: The financial sequelae of epilepsy among older Americans disproportionally affect minorities. Studies should examine contributors to high costs.